Taking Stock of SIM: Social Issues in Management Division of the Academy of Management. Issue 7 (September 2019) - Waddock, Sandra
This essay articulates two aspects of a changing Social Issues in Management (SIM) Division of the Academy of Management (AOM). First, the essay highlights the ways in which SIM's central focus has shifted and changed over the years. Then, it briefly looks at the forces that are currently shaping SIM within AOM, particularly in spreading what used to be the central core of SIM throughout AOM, and discusses some of the implications of this shift. This devolution of content suggests the need for further change that paradoxically does two things seemingly at odds with each other: brings SIM back to its normative roots and begins to articulate the type of distinctive orientation to business operating within society that might continue to differentiate SIM from other divisions within AOM in the future.